Applying clinical staging to young people who present for mental health care. Issue 1 (5th June 2012) - Hickie, Ian B.; Scott, Elizabeth M.; Hermens, Daniel F.; Naismith, Sharon L.; Guastella, Adam J.; Kaur, Manreena; Sidis, Anna; Whitwell, Bradley; Glozier, Nicholas; Davenport, Tracey; Pantelis, Christos; Wood, Stephen J.; et al.
Abstract Aim: The study aims to apply clinical staging to young people who present for mental health care; to describe the demographic features, patterns of psychological symptoms, disability correlates and clinical stages of those young people; and to report longitudinal estimates of progression from less to more severe stages. Methods: The study uses cross‐sectional and longitudinal assessments of young people managed in specialized youth clinics. On the basis of clinical records, subjects were assigned to a specific clinical 'stage' (i.e. 'help‐seeking', 'attenuated syndrome', 'discrete disorder' or 'persistent or recurrent illness'). Results: Young people (n = 209, mean age = 19.9 years (range = 12–30 years), 48% female) were selected from a broader cohort of n = 1483 subjects. Ten percent were assigned to the earliest 'help‐seeking' stage, 54% to the 'attenuated syndrome' stage, 25% to the 'discrete disorder' stage and 11% to the later 'persistent or recurrent illness' stage. The interrater reliability of independent ratings at baseline was acceptable (κ = 0.71). Subjects assigned to the 'attenuated syndrome' stage reported symptom and disability scores that were similar to those assigned to later stages. Longitudinally (median = 48 weeks), transition to later clinical stages were 11% of the 'help‐seeking', 19% of the 'attenuated syndrome' and 33% of the 'discrete disorder' groups. Conclusion: Among young people presenting for mental health care, most are clinically staged as having 'attenuated syndromes'. Despite access to specialized treatment, a significant number progress to more severe or persistent disorders.